Diklat dan Pengembangan Karir Menuju SDM Unggul di Lembaga Pendidikan Islam: Penelitian - Putri Kurniawati; Imam Junaris; Binti Maunah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to decide the essential concepts of HR training and career improvement, the sorts, stages, and challenges within the HR preparing and career advancement handle in Islamic instructive teach. The strategy utilized in this logical work is library investigate. The comes about of this research are that preparing and human asset advancement in instructive teach could be a arrangement of efficient exercises planned to progress the information, abilities and states of mind of instructing and instruction staff so that they are able to carry out their obligations and capacities more successfully and professionally. The types of training are pre-service, in-service, functional, technical and leadership training. And the types of career development are formal, non-formal and informal professional development. The stages in implementing training and development are Recruitment, Identifying learning needs, learning resources, and possible obstacles, Determining and formulating training and development objectives, Developing initial and final evaluation tools, Developing the sequence of training and development activities, Orientation for trainers, Carrying out evaluations for participants, Implementing training and development, Final evaluation, Evaluation of training programs.